Eying the future: Eye movement in past and future thinking. (August 2018) - El Haj, Mohamad; Lenoble, Quentin
Abstract: We investigated eye movement during past and future thinking. Participants were invited to retrieve past events and to imagine future events while their scan path was recorded by an eye-tracker. Past thinking triggered more fixation ( p < .05), and saccade counts ( p < .05) than future thinking. Past and future thinking triggered a similar duration of fixations and saccades, as well as a similar amplitude of saccades. Interestingly, participants rated past thinking as more vivid than future thinking ( p < .01). Therefore, the vividness of past thinking seems to be accompanied by an increased number of fixations and saccades. Fixations and saccades in past thinking can be interpreted as an attempt by the visual system to find (through saccades) and activate (through fixations) stored memory representations. The same interpretation can be applied to future thinking as this ability requires activation of past experiences. However, future thinking triggers fewer fixations and saccades than past thinking: this may be due to its decreased demand on visual imagery, but could also be related to a potentially deleterious effect of eye movements on spatial imagery required for future thinking.